2019
DOI: 10.1007/s00264-019-04363-5
|View full text |Cite
|
Sign up to set email alerts
|

How do global sagittal alignment and posture change after total hip arthroplasty?

Abstract: Background Postural change after total hip arthroplasty (THA) is still a matter of discussion. Previous studies have mainly concentrated on the pelvic motions. We report the post-operative changes of the global sagittal posture using pelvic, spinal, and lower extremities parameters. Methods 139 patients (primary THA, without previous spinal or lower extremity surgery) were included. We measured pelvic parameters [SS, sacral slope; PI, pelvic incidence; PT, pelvic tilt; APP angle, anterior pelvic plane angle] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
2
23
5
Order By: Relevance
“…11 Another study by Kim et al also showed decrease in SVA after THA, and in particular, found the SVA changes to present in the low and medium PI patients but not the high PI patients. 12 The present study was unable to demonstrate a difference between PI groups and change in global alignment parameters. This seemingly conflicting finding can be attributed to the fact that Kim et al did not perform any comparison in alignment parameters between PI groups, and thus could not conclude that PI significantly influenced alignment changes.…”
Section: Discussioncontrasting
confidence: 76%
“…11 Another study by Kim et al also showed decrease in SVA after THA, and in particular, found the SVA changes to present in the low and medium PI patients but not the high PI patients. 12 The present study was unable to demonstrate a difference between PI groups and change in global alignment parameters. This seemingly conflicting finding can be attributed to the fact that Kim et al did not perform any comparison in alignment parameters between PI groups, and thus could not conclude that PI significantly influenced alignment changes.…”
Section: Discussioncontrasting
confidence: 76%
“…Type 1 was defined as "neutral" with -1 cm < SSPT <1 cm for sagittal balance. As previously described in the literature, patients were categorized into 3 groups based on the PI: low PI < 45 , 45 < average PI < 65 , or high PI > 65 [24].…”
Section: Study Variablesmentioning
confidence: 99%
“…The importance of the preoperative sagittal pelvic tilt (SPT) assessment and its effect on the risk of total hip arthroplasty (THA) dislocation has been previously shown 1‐12 . The magnitude of the SPT during different daily activities is personalized based on the patients' functional anatomy 1,3‐5,10,13‐17 . SPT changes with spinal pathologies as well as spinal surgeries, but there is limited evidence regarding the magnitude of SPT change that can increase the risk for postoperative THA dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The magnitude of the SPT during different daily activities is personalized based on the patients' functional anatomy. 1,[3][4][5]10,[13][14][15][16][17] SPT changes with spinal pathologies as well as spinal surgeries, but there is limited evidence regarding the magnitude of SPT change that can increase the risk for postoperative THA dislocation. The criteria that is known is the spinal stiffness (SPT change less than 10°) that can increase the risk of dislocation.…”
Section: Introductionmentioning
confidence: 99%